The Role of International Arbitration Institutions in Resolving Business Disputes Between Countries - Arsal, Fathur Riyadhi (Indonesian Journal of Law and Justice, 2024)
Arbitration is an option that businesses frequently use to resolve conflicts. Arbitration, as an institution in the field of judicial proceedings outside of public courts, is a highly useful way of settling disputes or disagreements that arise in the fulfillment of agreements or contracts, particularly in both national and international private law. This arbitration organization is commonly utilized in commercial and investment transactions. In this research, the approach used is normative juridical, which evaluates and tests secondary facts in the form of positive law. This research is descriptive and analytical in nature. arbitration is a way of resolving a civil dispute outside the public courts based on an arbitration agreement made in writing by the parties to the dispute. Individuals or institutions can settle disputes through arbitration. Arbitration is increasingly being utilized to settle national and international commercial disputes. The role of international arbitration is facilitated by the existence of international arbitral institutions. These bodies include The London Court of International Arbiitration, The Court of Arbitation Of The International Chamber Of Commerce, The Arbitration Institute Of The Stockholm Chamber Of Commerce, and Indonesian National Arbitration Board.